MAPPING RESEARCH OPPORTUNITIES INNOVATION CAPABILITY SMALL MEDIUM ENTERPRISES: A BIBLIOMETRIC ANALYSIS AND NETWORK VISUALIZATION (JITK (Jurnal Ilmu Pengetahuan dan Teknologi Komputer), 2025)
Small and medium-sized business innovation research has a wide range of themes, and mapping innovation research is necessary to get an idea of the topics that are and will be developing. Bibliometric analysis of small and medium business innovation is one of the themes of trend research in the fields of business, economics, management, and computer science. Bibliometric analysis of the effects of innovation and open innovation on small and medium enterprises is one of the themes discussed, there has been no bibliometric analysis of the innovation ability of small and medium enterprises so the purpose of this study is to map research on the innovation ability of small and medium enterprises and to find opportunities for information technology innovation research themes for small and medium enterprises. The research method employed a bibliometric analysis,  with data collection from the Scopus database, resulting in   542 documents. The data analysis stage, with the help of the enhancement software, is open for the main data cleansing. Vos Viewer for network visualization and overlay visualization. Tableau for data visualization and descriptive analysis. The results of the bibliometric analysis, combined with network visualization, successfully map four research clusters of innovation capabilities and provide direction to researchers to determine emerging topics and future research. The use of big data analytics to increase innovation, business, and technology can improve organizational performance is one of the research themes that has the opportunity to be studied in the future
Keywords: bibliometric analysis; innovation capability; network visualization; small and medium enterprises; vos viewer